2018
DOI: 10.1002/slct.201801350
|View full text |Cite
|
Sign up to set email alerts
|

Natural Breviscapin, Mangiferin, and a Modified Mangostin Present Inhibitory Effect on Dipeptidyl Peptidase‐IV

Abstract: Type 2 diabetes was usually caused by inadequate secretion of insulin or insulin resistance in tissues and organs. About 90% diabetes belongs to type 2 diabetes, which is seriously harmful to human health. Dipeptidyl Peptidase‐IV (DPP‐IV) target have attracted much attention because of its ability to prevent type 2 diabetes (T2D). Clinical application of chemical synthetic medicines has different degrees of side effects. Therefore, the present evaluation aims to seek DPP‐IV inhibitors as the source of natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The most relevant aspects of this study are briey discussed in the next paragraph. Cyanidin 3-O-b-D-glucopyranoside (1), isoliquiritigenin (16), narcissoside (55), myricetin (65), and hyperoside (70) inhibited the enzyme higher than 50% at 200 mM. The IC 50 values of these avonoids were 81.05, 149.96, 166.52, 156.29, and 138.79 mM, respectively.…”
Section: Natural Products With Dpp-iv Inhibitory Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The most relevant aspects of this study are briey discussed in the next paragraph. Cyanidin 3-O-b-D-glucopyranoside (1), isoliquiritigenin (16), narcissoside (55), myricetin (65), and hyperoside (70) inhibited the enzyme higher than 50% at 200 mM. The IC 50 values of these avonoids were 81.05, 149.96, 166.52, 156.29, and 138.79 mM, respectively.…”
Section: Natural Products With Dpp-iv Inhibitory Propertiesmentioning
confidence: 99%
“…Kinetic analyses of cyanidin 3-O-b-D-glucopyranoside (1), isoliquiritigenin (16), narcissoside (55), and hyperoside (70) revealed that they were mixed-type inhibitors; furthermore, their competitive inhibition constants were lower than the uncompetitive ones. Thus, like most avonoids, these compounds preferred interacting with the enzyme's active site.…”
Section: Natural Products With Dpp-iv Inhibitory Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, a derivative with 2‐bromobenzoyl fragments at C‐3‐OH/C‐6‐OH positions demonstrated cytotoxic effects against four cancer cell lines [5a] . A derivative containing N ‐Boc‐ L– Met fragments at the same positions is a promising candidate for cardiovascular disease treatment, [5b] a derivative with 3‐methylbutane‐2,3‐diol moieties at positions C‐2 and C‐8 showed high inhibitory activity against dipeptidyl peptidase‐IV, which has been related to the development of type 2 diabetes mellitus [5c] …”
Section: Introductionmentioning
confidence: 99%